Kajian Sistem Pemasaran dan Hasil Tangkapan Nelayan Serta Tingkat Kesejahteraan Nelayan di Desa Lembur Barat, Kecamatan Alor Tengah Utara, Kabupaten Alor. - Melki Imamastri Puling Tang; Maharani Tersia Bely; Kessi Unab; Nelson Masy; Miranda Tonu (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
Fishermen are groups of individuals who carry out fishing and other aquatic biota in various types of waters, including fresh, brackish, and marine waters. Fishermen are communities that live on the coast and rely on marine catches for their livelihood. Although fraught with risks, the fishing profession is often passed down from generation to generation in Indonesia. However, their economic conditions are often affected by various factors, including climate problems such as famine seasons that occur every year. BPS 2013 data shows that fishermen and fishing communities play a large role in Indonesia's poverty rate. This study adopts a qualitative approach, by applying direct interviews with fishermen and document collection as data collection methods. Research findings show that fishermen face challenges in fishing, especially during high sea waves and lean seasons. In West Overtime Village, North Central Alor District, fishermen have difficulty finding fish because of the large rompong that affects the movement of fish in these waters. This condition encourages most fishermen to switch professions to become farmers to meet their daily needs. In small fishing communities, visible traits include the use of small-scale fishing gear, uncertain income, independent operations, and simple skills. Social and geographical isolation are also influencing factors, along with low levels of well-being. This research provides an in-depth understanding of the conditions and challenges faced by fishing communities and their impact on their welfare. Therefore, this research makes a valuable contribution in understanding the lives of fishermen in coastal Indonesia.